1996
DOI: 10.1016/0014-5793(96)00309-2
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structures of human procathepsin B at 3.2 and 3.3 Å resolution reveal an interaction motif between a papain‐like cysteine protease and its propeptide

Abstract: A wild-type human procathepsin B was expressed, crystallized in two crystal° forms and its crystal structure determined at 3.2 and 3.3 A resolution. The structure reveals that the propeptide folds on the cathepsin B surface, shielding the enzyme active site from exposure to solvent. The structure of the enzymaticaily active domains is virtually identical to that of the native enzyme [Musil et al. (1991) EMBO J. 10, 2321-2330]: the main difference is that the occluding loop residues are lifted above the body of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
128
0
2

Year Published

1996
1996
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(135 citation statements)
references
References 28 publications
5
128
0
2
Order By: Relevance
“…This agrees with crystallographic data showing that interaction of the proregion with rat cathepsin B involves residues Leu-41p-Gly-47p which are deeply buried in the substrate binding site [13]. According to these data and those for human cathepsin B [13,14], Cys-42p, which is the residue closest to the oxyanion hole, significantly contributes to propeptide binding by interacting with several hydrophobic groups of cathepsin B. Alkylation of Cys-42p in peptide PB8 resulted in a loss of inhibition (peptide PB8Acm). Peptide PB8Acm was also cleaved at the G47p-G48p site upon incubation with cathepsin B, but much more rapidly than peptide PBS.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…This agrees with crystallographic data showing that interaction of the proregion with rat cathepsin B involves residues Leu-41p-Gly-47p which are deeply buried in the substrate binding site [13]. According to these data and those for human cathepsin B [13,14], Cys-42p, which is the residue closest to the oxyanion hole, significantly contributes to propeptide binding by interacting with several hydrophobic groups of cathepsin B. Alkylation of Cys-42p in peptide PB8 resulted in a loss of inhibition (peptide PB8Acm). Peptide PB8Acm was also cleaved at the G47p-G48p site upon incubation with cathepsin B, but much more rapidly than peptide PBS.…”
Section: Resultssupporting
confidence: 90%
“…This explains the resistance of peptide PB11 to cleavage by the mature enzyme. The results obtained here using overlapping peptides spanning the cysteine proteinase proregion agree with those reported from crystal structures of human and rat procathepsin B [13,14]. This promising approach to designing more selective inhibitors of cysteine proteinases will be extended to the proregions of other papain-like proteinases, especially those of protozoan parasites like trypanosomes, that are involved in both spreading and host infection [30,31], but have no specific substrate or inhibitors that can selectively control their activity.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…In contrast to in vitro unfolding/refolding studies derived from the proregion of human procathepsin S and human procathepsin L (7,20), the insect cell system allows the assessment of protein folding under physiological conditions. Since folding was impaired in the case of the propeptide shortened by 23 amino acids and in the case of the propeptide mutated at position 23, we suggest that hydrophobic interactions between tryptophan 24p and tyrosine 183, as well as tyrosine 188 and phenylalanine 180, are necessary for folding and for anchoring the propeptide at the enzyme surface as suggested by Turk et al (21). In addition, tryptophan 24p was shown to form a hydrogen bond with the carbonyl group of glutamine 189 (21).…”
Section: Discussionsupporting
confidence: 56%
“…A similar but less systematic study of the interaction between cathepsin L and its propeptide also indicated that 20 and 15 amino acids could be removed from the N-and C-terminal parts of the propeptide without destroying the inhibitory activity [14]. Recently, the structure of human procathepsin B has been solved [18,19]. Assuming the propeptide interacts with cathepsin B in the same manner as the proregion in procathepsin B, the availability of the data presented in this work allows the functional evaluation of structural features evidenced by the proenzyme structure.…”
Section: N T T W Q Region C G T V L Regionmentioning
confidence: 99%